Visualiser des parcours migratoires à partir de récits de migrants, le cas des réfugiés syriens - David Lagarde (Cybergeo)
Since 2015, the so-called "migration crisis" in Europe has generated a large number of cartographic images, wrongly suggesting that the European Union is facing massive arrivals of asylum seekers. Moreover, these maps, based on aggregated data, tend to deliver a smooth and uniform image of migratory movements. These iconographies therefore ignore the vicissitudes of the journeys undertaken by people who are forced to travel along the irregular migration routes crisscrossing the Euro-Mediterranean area. These observations necessarily invite us to consider alternative modes of graphic representation, less Euro-centric, more humanizing and above all allowing us to recall the "migratory in-between" connecting the spaces of departure and settlement. This article presents a methodological protocol and graphic formalizations (itinerary maps, timelines and spatialized network diagrams) responding to these objectives. It is based therefore on qualitative data collected from a sample of Syrian refugees originating from the same locality in Syria: Deir Mqaren. The comparison of figures illustrating the different dimensions (spatial, temporal and relational) of their migratory journeys between Syria and Jordan highlights the effects of the closure of Jordanian borders on the routes taken since 2011 by Syrian exiles wishing to settle in Jordan.